Finite-β turbulence in Wendelstein 7-X enhanced by sub-threshold kinetic ballooning modes - P. Mulholland; M.J. Pueschel; J.H.E. Proll; K. Aleynikova; B.J. Faber; P.W. Terry; C.C. Hegna; C. Nührenberg (Nuclear Fusion)
Magnetic fluctuations affecting turbulence and transport, which are manifest at finite normalized plasma pressure β , pose a significant challenge to magnetic confinement fusion devices aiming to achieve high performance. Such regimes are not yet comprehensively understood in stellarator geometry. This work presents simulations of electromagnetic instabilities and high- β turbulence in the Wendelstein 7-X (W7-X) stellarator, showing how ion-temperature-gradient-driven (ITG) turbulence is enhanced by unconventional kinetic ballooning modes well below the ideal MHD threshold. These sub-threshold KBMs (stKBMs) become strongly excited in the turbulent state and enable higher fluxes via zonal-flow erosion. The threshold of stKBM impact on turbulent fluxes is heavily dependent on the pressure gradient, evidenced here by the enhanced destabilization and fluxes resulting from the inclusion of an electron temperature gradient. Understanding and controlling these stKBMs will be paramount for W7-X and potentially other stellarators to achieve optimal performance.